PERAN PEMERINTAH KOTA PEKANBARU DALAM MENYUKSESKAN PEKAN OLAHRAGA NASIONAL XVIII TAHUN 2012 - Dimas Putra Fauzi; Erman, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
National Sports Week (PON) is a national multi-sport event held 4 (four) years, and is the culmination of sports activities in order to increase and development of national sports achievements. Besides, PON act as a coaching outcome evaluation conducted by the Indonesian National Sports Committee (KONI) together Province Provincial Board (Pengprov) sports, KONI Regency / City and all of the components in each area. Where in 2011 the province of Riau to host PON XVIII, which became the center of Pekanbaru City of PON. The government's role in the success of Pekanbaru City National Sports Week XVIII of course highly charged. The purpose of this study was to determine the role of government in ensuring the success of Pekanbaru City National Sports Week XVIII and to know what are the factors that affect not optimal. This study uses qualitative research methods to include an assessment of descriptive file. Intake of informants in this study was purposive sampling namely retrieval techniques with particular data source, specific consideration is the person who is considered the most out of what we expect or as a ruler that will allow researchers to explore the object / social situation under study.Based on the research that has been done is used the theory of policy and policy evaluation. Researchers concluded Pekanbaru city government's role in the success of the National Games of the XVIII is not going well. Still there are constraints faced by the City of Pekanbaru is a problem related to the ability of local government officials, Public awareness is still lacking in the success of the National Sports Week XVIIIKeywords: policy evaluation, the National Sports Week XVIII